THE GROWTH RESPONSE AND YIELD OF WHITE EGGPLANT (Solanum melongena L.) TO THE APPLICATION OF CORN COB BOKASHI AND LIQUID ORGANIC FERTILIZER OF TEMPEH WASTE - Priatmojo, Tito; Sulistiani, Rini; Julia, Hilda (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2024)
White eggplant is a horticultural commodity that is widely distributed and consumed in Indonesia. It is included in hybrid varieties that have nutrients such as vitamins, calcium, phosphorus and fat. This study aims to obtain the maximum dose of corn cob bokashi and concentration of tempeh waste Liquid Organic Fertilizer (LOF) to increase the growth and yield of white eggplant (Solanum melongena L.). This study used a Randomized Block Design consisting of two factors, namely corn cob bokashi and LOF tempeh waste. Corn cob bokashi consists of levels: 0, 60, 90 and 120 g/plant. While for LOF tempeh waste consists of levels: 0, 250, 500 and 750 ml/polybag. The parameters observed were plant height, stem diameter, fruit diameter, number of fruits per plot, and fruit weight per plot. Observational data were analyzed using an analysis of variance and followed by a difference of means test according to Duncan's Multiple Range Test at p<0.05. The interaction of corn cob bokashi and tempeh waste LOF had no significant effect on all parameters. The recommended application of corn cob bokashi is 60 g/plant and LOF tempeh waste as much as 300 ml/polybag to obtain the optimum weight of eggplant fruit.